Pulse 1: Covid-19 and economic crisis - China's recovery and international response - Beatrice Tanjangco; Yue Cao; Rebecca Nadin; Linda Calabrese; Olena Borodyna (Overseas Development Institute (ODI), 2020)
This is the first report in ODI's Economic Pulse series. It explores China's international economic response to Covid-19 and analyses its international engagements, especially in developing countries, in light of shifts in the global economic and political landscape. Our review of China's economic response has an international focus due to the nature of the macroeconomic data, while project-level data and a policy review drill down into the effects of that response on developing countries.
Keywords: 330; COVID-19; Economic growth; China; Economics